Gambaran Motivasi Belajar pada Siswa SMP Negeri 1 Sukowono - Vikry Yusuf Rizki; Iin Ervina; Panca Kursistin Handayani (Indonesian Journal Publisher, 2023)
Learning motivation is the inner drive that a person needs to make decisions, have the drive to perform better, and to achieve goals by changing a person's behavior or personality depending on certain practices or experiences, especially students at the junior high school (SMP) education level. This age is between 12 and 15 years, where the child is already in the early stages of adolescence, at this time the child must undergo mental development and develop new attitudes towards discipline, values ​​and interests related to learning. A quantitative approach was taken to explore these objectives. The respondents in this research were students at SMP Negeri 1 Sukowono in grades 7 and 8 with a total of 152 students. The learning motivation scale is the main method of data collection in this research. Researchers used the Chernis and Goleman learning motivation scale consisting of several statement items regarding the urge to achieve something, commitment, initiative and optimism which was adapted by Gregorius (2014) totaling 50 items with a reliability value using Cronbach's Alpha of 0.942. The research results showed that some 80 students who had a learning motivation of 52.6% were in the low category and 72 students with a percentage of 47.4% were in the high category. This shows that the majority of students have relatively low learning motivation. Apart from that, students are also still not good at achieving implementation of aspects of their learning motivation, so efforts need to be made to improve every aspect of students' learning motivation.